Regression analysis of masked competing risks data under cumulative incidence function framework - Yousif, Yosra; Elfaki, Faiz A. M.; Hrairi, Meftah (Austrian Statistical Society, 2020)
In the studies that involve competing risks, somehow, masking issues might arise. That is, the cause of failure for some subjects is only known as a subset of possible causes. In this study, a Bayesian analysis is developed to assess the effect of risks factor on the Cumulative Incidence Function (CIF) by adopting the proportional subdistribution hazard model. Simulation is conducted to evaluate the performance of the proposed model and it shows that the model is feasible for the possible applications.